Assessment of coral health and lifeform composition using the CoralWatch method at Tunda Island, Banten, Indonesia - Mumtasya, Lenia; Fariz, Arya Nural; Mauludiyah; Idris (UIN Sunan Ampel Surabaya, 2026)
The waters surrounding Tunda Island support coral reef ecosystems ranging from low to moderate condition, which nevertheless provide essential ecological functions for marine life and coastal communities. Coral reefs are formed through the deposition of calcium carbonate produced by reef-building corals in symbiosis with Symbiodinium. These symbiotic algae perform photosynthesis, supplying a substantial portion of the energy required by their coral hosts while contributing to coral pigmentation and overall reef health. However, coral health is increasingly threatened by environmental stressors, including rising sea temperatures and declining water quality. This study aimed to assess the health status of corals at Tunda Island, Indonesia, using the CoralWatch method based on changes in coral tissue coloration. Data were collected through random surveys at six observation stations distributed around Tunda Island. The results showed that the coral community was dominated by branching corals (36.8%), followed by boulder (26.1%), plate (25.7%), and soft corals (11.4%). Coral health assessment indicated that most colonies were under moderate physiological stress, with color Scores 3 (34.2%) and 4 (54.4%) being the most frequently recorded categories, reflecting reduced pigmentation and an increased susceptibility to bleaching. These findings provide baseline information for long-term coral reef monitoring and highlight the importance of sustainable coastal management to reduce environmental stress and maintain coral reef resilience at Tunda Island.